Hubungan Paritas Dengan Kejadian Preeklampsia Pada Ibu Hamil - Renny Adelia Tarigan; Revi Yulia (LPPM STIKES Guna Bangsa, 2021)
Preeclampsia is a complication in pregnancy, childbirth and post partum which cannot be prevented and what can be done is to prevent the occurrence of more severe complications and avoid risk factors or predisposition to the occurrence of preeclampsia. Factors affecting preeclampsia are a history of hypertension and parity. The purpose of this study was to determine the relationship between history of parity with the incidence of preeclampsia. The design of this study was analytic with cross sectional design. The population in this study were all pregnant women in the Batam Puskesmas Batu Aji Batam City from February to July 2019, samples taken using purposive sampling as many as 88 respondents. The results of studies that have been carried out chi-square test for a history of and parity with preeclampsia obtained P value of 0.015 <α 0.05. The conclusion of this study is the relationship between history parity with preeclampsia in pregnant women. this research can be considered for making policies in an effort to improve the quality of health services in pregnant women.